On the Relationship Between Well-Being and Exercise Adherence for Children and Adolescents: A Systematic Mini Review - Chen, Jiping; Wu, Chenggang (Frontiers in Psychology, 2022)
Although the close positive relationship between well-being and exercise adherence has been confirmed by numerous studies, it is still unclear whether this relationship exists for children and adolescents, because previous research mainly focuses on adults. The present review systematically explored the relationship between well-being ranging from individual to social aspects and exercise adherence based on extant studies. Seven studies including both quantitative and qualitative studies were analyzed. The results showed that well-being was not related to exercise adherence as strongly as expected. In some cases, well-being was even negatively associated with exercise adherence. Limited sample size, insensitive measurement of exercise adherence, gender, and mental and physical condition of children and adolescents might partially influence the relationship between well-being and exercise studies. However, the studies at hand are still in their infancy. More studies on the relationship between well-being and exercise adherence are needed for children and adolescents, especially in non-western countries.